Design for profitability guidelines to cost effectively manage the development process of complex products - Elmoselhy, Salah A. M. (Industrial innovation series, 2016)
[This book] presents a design guideline for complex product design and development that enables you to cost-effectively improve the technical performance of your products and consequently improve your competitiveness in the marketplace as well as improve profitability.